2015
DOI: 10.1016/j.orggeochem.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of riverine suspended particulate matter on the branched glycerol dialkyl glycerol tetraether composition of lakes: The outflow of the Selenga River in Lake Baikal (Russia)

Abstract: Impact of riverine suspended particulate matter on the branched glycerol dialkyl glycerol tetraether composition of lakes: The outflow of the Selenga River in Lake Baikal (Russia)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…However, up to now there are only a few investigations of 5-and 6-methyl isomers in lake systems (De Jonge et al, 2015;Weber et al, 2015;Ding et al, 2016;Dang et al, 2016a;Russell et al, 2018), and the environmental controls (especially temperature control) on these isomers in Chinese lacustrine environments are yet to be deciphered. In particular, it is unknown if the relationships between the 5-and 6-methyl brGDGT isomers with environmental factors are the same in lakes as observed for soils.…”
Section: Introductionmentioning
confidence: 99%
“…However, up to now there are only a few investigations of 5-and 6-methyl isomers in lake systems (De Jonge et al, 2015;Weber et al, 2015;Ding et al, 2016;Dang et al, 2016a;Russell et al, 2018), and the environmental controls (especially temperature control) on these isomers in Chinese lacustrine environments are yet to be deciphered. In particular, it is unknown if the relationships between the 5-and 6-methyl brGDGT isomers with environmental factors are the same in lakes as observed for soils.…”
Section: Introductionmentioning
confidence: 99%
“…Dang et al (2016), for example, found a moisture control on 6-methyl brGDGT distributions in semi-arid and arid soils. Results of the analyses of sources and distributions of 6-methyl brGDGTs in coastal marine and lake sediments suggest that brGDGTs are universally produced in the water column (De Jonge et al, 2015a, 2015b, 2016Sinninghe Damsté, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since bGDGTs are membrane lipids produced by bacteria, sources of bGDGTs in lake sediments can be diverse, comprising, for example, soils (Weijers et al, 2007b), peats (Weijers et al, 2006;Naafs et al, 2017), and aquatic environments (Zhu et al, 2011;Buckles et al, 2014;Sinninghe Damsté, 2016). Therefore, the provenance of bGDGTs should be assessed before using bGDGTs in paleotemperature reconstruction (Yang et al, 2013;Zell et al, 2013;De Jonge et al, 2015;Warden et al, 2016). It has been reported that the ternary diagram of tetra-, penta-, and hexa-methylated bGDGTs can separate bGDGTs from soils by input from land (e.g., by riverine transport) or by aquatic (in situ) production (Sinninghe Damsté, 2016).…”
Section: Provenance Of Glycerol Dialkyl Glycerol Tetraethersmentioning
confidence: 99%